Iniciação científica júnior: uma proposta de atividade de aprendizagem - Silva, Jeferson Junio Batista (2021)
The basis of scientific knowledge is the questions raised with the observations made in the environment, curiosity. In this sense, it is understood that the work of scientific initiation with students of basic education can contribute for them to have contact with aspects of academic research, with the development of oral and written language, the appropriation of knowledge in several other areas of knowledge, in addition to valuing collaborative work, that is, the development of theoretical thinking itself. This work is based on the assumptions of the Historical-Cultural Theory, in particular the Activity Theory, considering the thesis that the human being is an integral being, constituted of several dimensions that are intertwined: biological, social, spiritual and emotional. Thus, it is established as a problem of this research: What principles should be considered so that the organization of junior scientific initiation (ICJ) with students of the final years of elementary school II (8th and 9th years) and high school become an activity of learning? Seeking to answer this question, an ICJ group was created, having been nominated as Junior Scientific Initiation Group in Sciences and Mathematics (GICEM). The actions of students participating in the group in the years 2018 to 2020 were analyzed, making it possible to understand which roles should be played by students and teachers for ICJ to be in fact a learning activity. The development of this research contributed directly to the professional and personal training of all those involved, students, teachers and the researcher himself. From this research, a website was produced as an educational product, allowing the production of GICEM students and teachers to be made available, in addition to the group's own constitution history.